Evaluation of light transmission through translucent and opaque posts - Galhano, G. A.; de Melo, R. M.; Barbosa, S. H.; Zamboni, S. C.; Bottino, M. A. [UNESP]; Scotti, R. (Operative Dentistry Inc, 2008)
Objectives: The transmission of light through translucent posts was observed, and the microhardness of light-cured cement used to secure these posts was evaluated at different depths. Methods: Fifteen single-rooted standard bovine teeth, 16 mm in size, were used. The root canals were prepared using #3 drills Light-Post (five teeth) and Aestheti Post (five teeth) systems (BISCO), with a working-length of 12 mm. In five teeth, translucent posts were cemented (Light-Post #2), while another five teeth received opaque posts (Aestheti Post #2). The roots were painted with black nail varnish to prevent the passage of light through the lateral walls of the roots. The root canals of all the specimens were treated with the All-Bond 2 adhesive system (BISCO) and cemented with light-cured cement (Enforce, Dentsply). All the roots were transversally cut to obtain six specimens 1.5 mm thick. Every two sections corresponded to a specific region of the root (cervical, middle, apical), making it possible to observe the cement microhardness at different levels. The groups (n=10) were defined as: G1: translucent post (TP)/cervical region; G2: TP/middle region; G3: TP/apical region; G4: Opaque post (OP)/cervical region; G5: OP/middle region; G6: PO/apical region. Five root canals were only filled with cement for use as a control (G7). Then, Vickers microhardness analyses were performed. Results: In G3, G5 and G6, the cement was not sufficiently hard to allow for microhardness analysis. When submitted to the ANOVA test, G1 (35.07), G2 (24.28) and G4 (28.64) presented no statistical differences. When the previous groups were compared to G7 (51.00) using the Kruskal-Wallis test, a statistical difference was found. Conclusion: Translucent posts allow cement polymerization up to the middle portion of the root.